Evaluation of Tie Support at Transition Zones. Issue 1 (January 2015) - Stark, Timothy D.; Wilk, Stephen T.; Sussmann, Theodore R.
This paper discusses two instrumentation techniques, linear variable differential transformers (LVDTs) and accelerometers, used to monitor and evaluate track structure behavior with the goal of nondestructively and quickly identifying track structural problems that eventually cause track geometry problems. LVDT results at a poorly performing bridge approach and corresponding open track site are used to show a relationship between poor tie support and the observed permanent vertical displacements. The existence of a gap between the bottom of the tie and the top of the ballast is expected to increase permanent ballast vertical displacements because of increased loads and vibration applied to the underlying ballast. Similarly, accelerometers show larger peak tie accelerations at ties with tie–ballast gaps and suggest that poor tie support increases applied loads to underlying ballast. Collected field data show that the tie–ballast gap can increase with time, which results in progressive loss of tie support at that tie and an increasing load on adjacent ties because of redistribution of wheel loads. The results show the need for a nondestructive monitoring system to be used with existing track geometry detection systems to improve identification of poorly supported ties. This system will guide maintenance to reduce the gap, because even a small gap can decrease tie and ballast performance and thus require remediation of a track section rather than a single tie.